Malaria from hyperendemicity to elimination in Hekou County on China–Vietnam border: an ecological study. (December 2017) - Xu, Jian-Wei; Li, Jian-Jie; Guo, Hong-Ping; Pu, Shu-Wei; Li, Shu-Mei; Wang, Rong-Hua; Liu, Hui; Wang, Wei-Jia
Abstract Background Malaria control and elimination are challenged by diversity and complexity of the determinants on the international border in the Great Mekong Sub-region. Hekou, a Chinese county on the China–Vietnam border, was used to document Chinese experiences and lessons for malaria control and elimination. Methods The design was an ecological study. Malaria burden before 1951 and procedures of 64 years (1952–2015) from malaria hyperendemicity to elimination are described. Single and bilinear regression analysis was utilized to analyse the relationship between the annual malaria incidence (AMI) and gross domestic product (GDP), urbanization rate, and banana planting area (BPA). Results There was a huge malaria burden before 1951. AMI was reduced from 358.62 per 1000 person-years in 1953 to 5.69 per 1000 person-years in 1960. A system of primary health services, comprising three levels of county township hospitals and village health stations maintained malaria control and surveillance activities in changing political and social-economic settings. However, potential under-reported of malaria and market-oriented healthcare led to a malaria epidemic in 1987. Strong political commitment reoriented malaria from a control to an elimination programme. High coverage of malaria intervention and population access to intervention was crucial for malaria control and elimination; meanwhile, AMI was closely associated with socio-economic development, correlation coefficients (R) −0.6845 (95% CI −0.7978, −0.6845) for national GDP, −0.7014 (−0.8093, −0.7014) for national urbanization rate and −0.5563 (−0.7147, −0.3437) for BPA. Conclusions Multifactor, including political commitment, effective interventions, social and economic development and changing ecological environment, and the complicated interactions between these factors contribute to malaria elimination in Hekou County.